TMT-Based Proteomic Analysis of Plasma from Children with Rolandic Epilepsy. (7th October 2020) - Sun, Ji; Jiang, Tiechao; Gu, Feng; Ma, Dihui; Liang, Jianmin
Abstract : Rolandic epilepsy is one of the most common epileptic syndromes in childhood. We used TMT-based proteomics and bioinformatics analysis to identify the differentially expressed proteins in plasma of children with Rolandic epilepsy. Our aim was to provide a molecular basis for exploring possible mechanisms underlying the pathogenesis of epilepsy. Subjects were divided into two groups (five in each): patients with Rolandic epilepsy as cases and patients with migraine as controls. Total proteins were extracted and quantitatively labeled with TMT, then analyzed using liquid chromatography mass spectrometry. Bioinformatics analysis was used to identify the hub genes. A total of 752 proteins were identified, of which 670 contained quantitative proteins. 217 differentially expressed proteins were identified, 46 of which were only upregulated in more than two groups and 111 of which were only downregulated in more than two groups. Bioinformatics analysis revealed top 10 hub genes in the up- and downregulated groups, respectively. Our study demonstrates that some differentially expressed proteins are associated with epilepsy. Activation of acute-phase or innate immune response and complement and fibrinogen systems and repression of glycolysis, lipoprotein metabolism, and antioxidant activity may play a role in the development of epilepsy.